Desenvolvimento de um biossensor para detecção de Salmonella em alimentos - Silva, Gabrielle Batista Landim (2023)
Salmonellosis is a disease transmitted by contaminated food and is one of the main causes of infections worldwide. To ensure public health, early detection of pathogens is crucial. However, current detection methods are laborious and time-consuming, impacting the entire food chain. In this study, we developed a biosensor for rapid detection of Salmonella in food samples. The detection system is based on lateral flow technology with gold nanoparticles as an optical transducer and antibodies as antigen recognition molecules, with results obtained in just 15 minutes after inserting the strip into the sample. The developed biosensor has selectivity in relation to other microorganisms such as Escherichia coli and Staphylococcus aureus, sensitivity, with a visible detection limit of 10³ CFU.ml⁻¹ and quantitative of 1 CFU.ml⁻¹, values below existing commercial tests and 100% of repeatability. It is fast and reliable and can be a favorable alternative for Salmonella screening in food to ensure food safety.